ҚАНДЛИ ДИАБЕТ 2-ТИПИГА ЗАМОНАВИЙ ТИББИЙ ЁНДАШУВЛАР - Ахмедов Аббос Ботир угли; Ахмедова Мадина Зокир кизи (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
• International Diabetes Federation. IDF Diabetes Atlas, 10th edition. Brussels: IDF; 2021. Доступно: https://www.diabetesatlas.org • Saeedi P., Petersohn I., Salpea P., et al. Global and regional diabetes prevalence estimates for 2019 and projections for 2030 and 2045. Diabetes Research and Clinical Practice. 2019;157:107843. • DeFronzo R.A., Ferrannini E., Groop L., et al. Type 2 diabetes mellitus. Nature Reviews Disease Primers. 2015;1:15019. • Blonde L., Umpierrez G.E., Reddy S.S., et al. American Association of Clinical Endocrinology clinical practice guideline: developing a diabetes mellitus comprehensive care plan -2022 update. Endocrine Practice. 2022;28(10):923-1049. • American Diabetes Association Professional Practice Committee. Standards of care in diabetes -2024. Diabetes Care. 2024;47(Suppl. 1):S1-S321. • Дедов И.И., Шестакова М.В., Майоров А.Ю. и др. Сахарный диабет 2 типа у взрослых. Клинические рекомендации. Сахарный диабет. 2022;25(2):124-156. • Gerstein H.C., Sattar N. Cardiovascular and kidney outcomes with finerenone in chronic kidney disease and type 2 diabetes: the FIDELIO-DKD randomised trial. Lancet Diabetes & Endocrinology. 2021;9(10):669-670. • Marx N., Federici M., Schütt K., et al. 2023 ESC Guidelines on the management of cardiovascular disease in patients with diabetes. European Heart Journal. 2023;44(39):4043-4140. • Mannucci E., Candido R., delle Monache L., et al. 2023 update on Italian guidelines for the treatment of type 2 diabetes. Acta Diabetologica. 2023;60(9):1129-1154. • Sun H., Saeedi P., Karuranga S., et al. IDF Diabetes Atlas: Global, regional and country-level diabetes prevalence estimates for 2021 and projections for 2045. Diabetes Research and Clinical Practice. 2022;183:109119.